Terapie kritické koncetinové ischemie u pacientů se syndromem diabetické nohy pomocí autologních kmenových bunek - Dubský, M; Jirkovská, A; Bém, R; Pagácová, L; Fejfarová, V; Varga, M; Skibová, J; Langkramer, S; Syková, E (Vnitrni lekarstvi, 2011)
AIM: The aim of our study was to assess safety and effectiveness of therapy of critical limb ischaemia by autologous stem cells and evaluation of potential adverse events. METHODS: Fourteen patients were included into the study (11 men, 3 women, mean age 61.9 +/- 9.6 years, mean diabetes duration 23.5 +/- 11.1 years, mean glycated hemoglobin 6 +/- 1%). Eight patients were treated by bone marrow stromal cells, 6 patients by peripheral blood progenitor cells after stimulation by filgrastim. The suspension of stem cells was then applied into the muscles of ischemic limbs. We evaluated transcutaneous oxygen tension (TcPO2), subjective pain sensation assessed by Visual Analog Scale (VAS) and wound healing. RESULTS: TcPO2 significantly increased in all patients from 10 +/- 8.7 mm Hg before the treatment to 39.4 +/- 9.5 mm Hg after 6 months (p = 0.0005) after stem cell therapy. We also observed significant area defect reduction and pain decrease during the follow-up period. Median of area defect was reduced from 4.3 (0.7 - 31.7) before the treatment to 0.06 (0 - 0.5) cm2 after 6 months from the treatment (p = 0.0078). Decrease in rest pain was observed in all patients, mean VAS decreased from 5.3 +/- 1.8 to 1.1 +/- 1.3 after 6 months (p = 0.002). CONCLUSION: Our study suggests that stem cell therapy of diabetic foot disease is an effective therapeutic option with no adverse events for patients with severe peripheral arterial disease. This treatment leads to increase of transcutaneous oxygen tension, improves wound healing and decreases the rest pain.
Keywords: bérec; Pain Measurement; Humans; Blood Gas Monitoring, Transcutaneous; lidé středního věku; transkutánní měření krevních plynů; Ischemia; Female; Aged; Diabetic Foot; diabetická noha; senioři; lidé; transplantace kmenových buněk; ženské pohlaví; Male; Middle Aged; komplikace diabetu; Diabetes Complications; ischemie; Stem Cell Transplantation; mužské pohlaví; měření bolesti; Leg